2021
DOI: 10.3390/jcm10173898
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Outcome of Patients with TPO Mutations

Abstract: Introduction: Thyroid peroxidase (TPO) deficiency is the most common enzymatic defect causing congenital hypothyroidism (CH). We aimed to characterize the long-term outcome of patients with TPO deficiency. Methods: Clinical and genetic data were collected retrospectively. Results: Thirty-three patients with primary CH caused by TPO deficiency were enrolled. The follow-up period was up to 43 years. Over time, 20 patients (61%) developed MNG. Eight patients (24%) underwent thyroidectomy: one of them had minimal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…analysing the long-term outcome of 33 CH patients with TPO mutations showed that 61% of them developed MNG over time at an average age of 8,6 years ( 19 ) without an association with higher TSH levels. In this case series, thyroidectomy was performed in eight patients (24%) leading to the diagnosis of a minimally invasive follicular carcinoma and seven cases of follicular hyperplasia or adenoma ( 19 ). Thus, the high rate of MNG development and the risk for thyroid carcinoma indicates the need for regular ultrasound and a long-term follow up in these patients ( 19 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…analysing the long-term outcome of 33 CH patients with TPO mutations showed that 61% of them developed MNG over time at an average age of 8,6 years ( 19 ) without an association with higher TSH levels. In this case series, thyroidectomy was performed in eight patients (24%) leading to the diagnosis of a minimally invasive follicular carcinoma and seven cases of follicular hyperplasia or adenoma ( 19 ). Thus, the high rate of MNG development and the risk for thyroid carcinoma indicates the need for regular ultrasound and a long-term follow up in these patients ( 19 ).…”
Section: Discussionmentioning
confidence: 99%
“…In this case series, thyroidectomy was performed in eight patients (24%) leading to the diagnosis of a minimally invasive follicular carcinoma and seven cases of follicular hyperplasia or adenoma ( 19 ). Thus, the high rate of MNG development and the risk for thyroid carcinoma indicates the need for regular ultrasound and a long-term follow up in these patients ( 19 ). Although most patients affected by PTHS develop benign nodular goiter ( 3 , 20 , 21 ), our patient underwent total thyroidectomy at the age of seven without previously performing a cytological investigation by fine-needle aspiration.…”
Section: Discussionmentioning
confidence: 99%